Situational Judgment Tests - CHAN, David (Institutional Knowledge at Singapore Management University, 2007)
Many work situations require the job incumbent to make a judgment about aspects of the situation and respond to the practical situational demands. An effective response to the practical demands of a situation may require the appropriate use of some combination of one's abilities and other personal attributes. Situational judgment tests (SJTs) are psychometric tests that are specifically designed to assess individual differences in this overall ability to make effective judgments or responses to a wide variety of situations.